Time series forecasting based on optimized LLM for fault prediction in distribution power grid insulators - Matos-Carvalho, João P.; Stefenon, Stefano Frizzo; Valderi Leithardt; Kin-Choong Yow (arXiv is a free distribution service and an open-access archive for nearly 2.4 million scholarly articles, 2025)
Surface contamination on electrical grid insulators leads to an increase in leakage current until an electrical discharge occurs, which can result in a power system shutdown. To mitigate the possibility of disruptive faults resulting in a power outage, monitoring contamination and leakage current can help predict the progression of faults. Given this need, this paper proposes a hybrid deep learning (DL) model for predicting the increase in leakage current in high-voltage insulators. The hybrid structure considers a multi-criteria optimization using tree-structured Parzen estimation, an input stage filter for signal noise attenuation combined with a large language model (LLM) applied for time series forecasting. The proposed optimized LLM outperforms state-of-the-art DL models with a root-mean-square error equal to 2.24×10−4 for a short-term horizon and 1.21×10−3 for a medium-term horizon.